2013
DOI: 10.1038/sc.2013.43
|View full text |Cite
|
Sign up to set email alerts
|

Permanent mechanical deformation of an intrathecal baclofen pump secondary to scuba diving: a case report

Abstract: Study design: Case report. Objectives: To describe the case of a spinal cord injury patient that went scuba diving resulting in a mechanical deformation of his intrathecal baclofen pump. Setting: University Hospitals Leuven, Belgium. Methods: Case report. Results: Diving below 10 meters of depth can result in irreversible mechanical damage of the drug reservoir of an intrathecal baclofen pump. Conclusion: Patients with an intrathecal baclofen pump should be warned for the risks associated with scuba diving and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Whole‐body shock wave lithotripsy is a precaution for intrathecal delivery systems due to the potential for electronic damage to the device by the sound waves. Exposure to pressures from SCUBA diving and hyperbaric oxygen therapy places the patient at risk for pump damage or temporary under‐ or overinfusion, particularly if exposure is repeated and the reservoir is not close to full volume . There is also a case report of battery failure of an intrathecal delivery system following exposure to high‐dose radiation therapy .…”
Section: Diagnostic Evaluation Processmentioning
confidence: 99%
“…Whole‐body shock wave lithotripsy is a precaution for intrathecal delivery systems due to the potential for electronic damage to the device by the sound waves. Exposure to pressures from SCUBA diving and hyperbaric oxygen therapy places the patient at risk for pump damage or temporary under‐ or overinfusion, particularly if exposure is repeated and the reservoir is not close to full volume . There is also a case report of battery failure of an intrathecal delivery system following exposure to high‐dose radiation therapy .…”
Section: Diagnostic Evaluation Processmentioning
confidence: 99%
“…Implanted pumps such as IDD pumps are unique even among these neurological devices, with an additional consideration arising from the possibility that hyperbaric exposure could result in a change in reservoir size during compression and decompression phases of treatment, leading to rupture or warping of the device and subsequent malfunction or improper refilling and storage of medication for subsequent use [15,17,18,27,28]. From a technical point of view, prior to the application of HBOT, formal clearance should be obtained from the manufacturer whenever possible regarding feasibility and maximum tolerable pressure for each specific device to allow for accurate assessment and minimization of possible complications such as hardware malfunctions or reservoir deformities.…”
Section: Discussionmentioning
confidence: 99%
“…IDDSs should be refilled prior to high-pressure exposure to prevent deformation of the device. Draulans et al reported a case of irreversible loss of drug reservoir capacity due to collapse of the bottom shield after scuba diving 4. It is possible that the first case of indentation of IDDS could possibly be prevented if the above protocol was followed.…”
Section: Discussionmentioning
confidence: 99%
“…This has been described in the case of stuck bellows and indentation of the IDDS after scuba diving 4. No return product analysis was available.…”
Section: Discussionmentioning
confidence: 99%